Privacy-Preserving Collection and Evaluation of Log Files - Koch, Angelina

Förderung von digitalisierungsbezogenen Kompetenzen von angehenden Physiklehrkräften mit dem SQD-Modell im Projekt DiKoLeP - Weiler, David; Burde, Jan-Philipp; Große-Heilmann, Rike Isabel; Lachner, Andreas; Riese, Josef; Schubatzky, Thomas (Lehr-Lern-Labore und Digitalisierung)

The Impact of the German Fuel Discount on Prices at the Petrol Pump - Seiler, Volker; Stöckmann, Nico (German Economic Review)
Abstract This paper investigates the price impact of the fuel discount in Germany, which was introduced between June and August 2022 to partially compensate increased energy costs. Using the augmented synthetic control method (ASCM) to construct the counterfactual, we provide quantitative evidence to the heated debate concerning the impact of this policy tool and find the fuel discount to have decreased consumer prices of petrol (diesel) by at least 0.30 euro per litre (0.10 euro per litre) on average. The results are robust to various sensitivity checks. Thus, oil companies and petrol stations decreased prices for consumers and passed on about 85 % (65 %) of the discount in case of petrol (diesel). Moreover, we do not find signs of excessive price increases in anticipation of the fuel discount.
Keywords: Economics and Econometrics

Glaubende Grundhaltung als Zugang zum IslamTheologische Kompetenzen von islamischen Religionslehrkräften - Kamcili-Yildiz, Naciye (Islamischer Religionsunterricht in Deutschland)

Powder Production via Atomisation and Subsequent Laser Powder Bed Fusion Processing of Fe+316L Steel Hybrid Alloy - Pramanik, Sudipta; Andreiev, Anatolii; Hoyer, Kay-Peter; Krüger, Jan Tobias; Hengsbach, Florian; Kircheis, Alexander; Zhao, Weiyu; Fischer-Bühner, Jörg; Schaper, Mirko (Powders)
The current investigation shows the feasibility of 316L steel powder production via three different argon gas atomisation routes (closed coupled atomisation, free fall atomisation with and without hot gas), along with subsequent sample production by laser powder bed fusion (PBF-LB). Here, a mixture of pure Fe and atomised 316L steel powder is used for PBF-LB to induce a chemical composition gradient in the microstructure. Optical microscopy and μ-CT investigations proved that the samples processed by PBF-LB exhibit very little porosity. Combined EBSD-EDS measurements show the chemical composition gradient leading to the formation of a local fcc-structure. Upon heat treatment (1100 °C, 14 h), the chemical composition is homogeneous throughout the microstructure. A moderate decrease (1060 to 985 MPa) in the sample’s ultimate tensile strength (UTS) is observed after heat treatment. However, the total elongation of the as-built and heat-treated samples remains the same (≈22%). Similarly, a slight decrease in the hardness from 341 to 307 HV1 is observed upon heat treatment.

3D-structure of intermetallic interface layer in Al–steel clad material - Šlapáková, Michaela; Kihoulou, Barbora; Veselý, Jozef; Minárik, Peter; Fekete, Klaudia; Knapek, Michal; Králík, Rostislav; Grydin, Olexandr; Stolbchenko, Mykhailo; Schaper, Mirko (Vacuum)
This paper reveals the 3D character of the intermetallic layer at the aluminum–steel interface which pops up above the original sample surface during annealing. Popping out of the intermetallics was proven using atomic force microscopy. The phase expands out of the plane due to the exothermic formation of the Al5Fe2 phase and the feasibility of surface diffusion. Milling by a focused ion beam enabled the comparison of the chemical composition of the surface layer with the bulk interface, showing no difference. The growth direction is both towards aluminum and steel — the main diffusion flux is from aluminum towards steel, and the new intermetallic phase emerges at the steel side. The shortage of Al atoms causes a shift of the intermetallic as a whole towards aluminum.
Keywords: Al-steel clad; twin-roll casting; 3D characterization; atomic force microscopy; diffusion direction; surface growth

Powder bed fusion of soft-magnetic iron-based alloys with high silicon content - Andreiev, Anatolii; Hoyer, Kay-Peter; Hengsbach, Florian; Haase, Michael; Tasche, Lennart; Duschik, Kristina; Schaper, Mirko (Journal of Materials Processing Technology)
Keywords: Industrial and Manufacturing Engineering; Metals and Alloys; Computer Science Applications; Modeling and Simulation; Ceramics and Composites

Crowdwork in the Age of Algorithms – How Algorithmic Requesters affect the Meaningfulness of Crowdwork - Laux, Florian; Haff, André; Kundisch, Dennis

Heinrich A. Meyer-Reichenau: "Der kecke Griff nach der Bibel und die davongetragene Beute". Studien zur Predigt und Theologie des Bremer Pfarrers Gottfried Menken (1768-1831) - Schroeter-Wittke, Harald (Jahrbuch für Evangelische Kirchengeschichte des Rheinlandes)

Katharina Herrmann: Gesungene Katechese. Kommunikation durch Popularisierung. Kulturelle Repräsentation eines engagierten protestantischen Christentums im Neuen Geistlichen Lied - Schroeter-Wittke, Harald (Jahrbuch für Evangelische Kirchengeschichte des Rheinlandes)

Thorsten Knauth/Rainer Möller/Annebelle Pithan (Hg.), Inklusive Religionspädagogik der Vielfalt. Konzeptionelle Grundlagen und didaktische Konkretionen. Münster/New York 2020 - Schroeter-Wittke, Harald (Zeitschrift für Pädagogik und Theologie)

Volker Leppin: Repräsentation und Reenactment. Spätmittelalterliche Frömmigkeit verstehen - Schroeter-Wittke, Harald (Jahrbuch für Evangelische Kirchengeschichte des Rheinlandes)

Bomb the System! Politische Pieces als Partizipationspraktik im öffentlichen Raum - Niemann, Sven (Kunst und Politik. Jahrbuch der Guernica-Gesellschaft. Schwerpunkt: Politisches Graffiti.)

IngridKG: A FAIR Knowledge Graph of Graffiti - Sherif, Mohamed Ahmed; da Silva, Ana Alexandra Morim; Pestryakova, Svetlana; Ahmed, Abdullah Fathi; Niemann, Sven; Ngomo, Axel-Cyrille Ngonga (Scientific Data)
Abstract Graffiti is an urban phenomenon that is increasingly attracting the interest of the sciences. To the best of our knowledge, no suitable data corpora are available for systematic research until now. The Information System Graffiti in Germany project ( Ingrid ) closes this gap by dealing with graffiti image collections that have been made available to the project for public use. Within Ingrid , the graffiti images are collected, digitized and annotated. With this work, we aim to support the rapid access to a comprehensive data source on Ingrid targeted especially by researchers. In particular, we present Ingrid KG, an RDF knowledge graph of annotated graffiti, abides by the Linked Data and FAIR principles. We weekly update Ingrid KG by augmenting the new annotated graffiti to our knowledge graph. Our generation pipeline applies RDF data conversion, link discovery and data fusion approaches to the original data. The current version of Ingrid KG contains 460,640,154 triples and is linked to 3 other knowledge graphs by over 200,000 links. In our use case studies, we demonstrate the usefulness of our knowledge graph for different applications.
Keywords: Library and Information Sciences; Statistics; Probability and Uncertainty; Computer Science Applications; Education; Information Systems; Statistics and Probability

A Pulsed Lidar System With Ultimate Quantum Range Accuracy - Kruse, Stephan; Serino, Laura; Folge, Patrick Fabian; Echeverria Oviedo, Dana; Bhattacharjee, Abhinandan; Stefszky, Michael; Scheytt, J. Christoph; Brecht, Benjamin; Silberhorn, Christine (IEEE Photonics Technology Letters)
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics; Electronic; Optical and Magnetic Materials

INGRID—Archiving Graffiti in Germany - Niemann, Sven (Document | Archive | Disseminate Graffiti-Scapes)

A parametrisation method for high-order phase reduction in coupled oscillator networks - von der Gracht, Sören; Nijholt, Eddie; Rink, Bob (arXiv:2306.03320)
We present a novel method for high-order phase reduction in networks of weakly coupled oscillators and, more generally, perturbations of reducible normally hyperbolic (quasi-)periodic tori. Our method works by computing an asymptotic expansion for an embedding of the perturbed invariant torus, as well as for the reduced phase dynamics in local coordinates. Both can be determined to arbitrary degrees of accuracy, and we show that the phase dynamics may directly be obtained in normal form. We apply the method to predict remote synchronisation in a chain of coupled Stuart-Landau oscillators.

Literature Reviews in Operations Research: A New Taxonomy and a Meta Review - Schryen, Guido; Sperling, Martina (Computers & Operations Research)

Prozesskettensimulation für das Clinchen mit beweglicher Matrize - Rossel, Moritz Sebastian; Meschut, Gerson (BLECHE+ROHRE+PROFILE)

RELD: A Knowledge Graph of Relation Extraction Datasets - Ali, Manzoor; Saleem, Muhammad; Moussallem, Diego; Sherif, Mohamed; Ngonga Ngomo, Axel-Cyrille